METABOLIC SYNDROME AND CEREBRAL STROKE IN KAZAKHSTAN: SOME MANAGEMENT FACTORS - B. B. Benberin; T. A. Vochshenkova; G. A. Yermakhanova; E. P. Yakovenko; A. A. Akhetov; N. A. Shanazarov; A. Y. Naurazbayeva; B. R. Bimbetov (Scientific Journal of Pedagogy and Economics, 2018)
The purpose of the paper is to study the specific features of the influence of certain factors on mortality due to cerebral stroke (CS) in different regions of Kazakhstan. Materials and methods. The data on incidence and mortality in CS from the national statistics of Kazakhstan were used. The analysis was carried out using the methods of descriptive and analytical statistics. Results. Three groups of regions of Kazakhstan have been formed depending on the level of the specific gravity of the CS in the overall structure of deaths for 2012-2016. The ratio of incidence to mortality in Kazakhstan indicated stable dynamics from 2012 to 2016 among the population. The data obtained suggest that among the generally accepted medical and non-medical measures, the management of the development of metabolic disorders before the risks of aging-associated diseases can be used to manage their mortality, including from a cerebral stroke.